ANALISIS TINGKAT KESEHATAN KOPERASI PEGAWAI REPUBLIK INDONESIA TUWUH BLORA BERDASARKAN PERATURAN MENTERI NOMOR: 14/Per/M.KUKM/XII/2009 - Dedi Wijaya (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
This study aims to determine the soundness of the cooperative, which refers to the Regulation of the Minister of Cooperatives and Small and Medium Enterprises No. 14/PER/M.KUKM/XII/2009, namely capital, asset quality aspects, management aspects, aspects of efficiency, liquidity aspects , aspects of independence and growth as well as aspects of the identity of cooperatives. Object of this research is the official cooperation of the Republic of Indonesia (KPRI) Tuwuh located in Blora. The method used is descriptive research that focuses on financial ratios derived from the financial statements of the cooperative in 2014. The results of the studies conducted show a health cooperative in 2014 received a score of 80.50. This indicates a healthy level of health cooperatives. However Tuwuh Blora cooperative has not been audited by the firm, then lowered one rank achievements to be fairly healthy. Keywords: Ministerial Regulation No: 14/Per/M.KUKM/XII/2009, Soundness, KPRI Tuwuh Blora